Pecalang Existence in Keeping Public Order and Safety of Pakraman on the Celebration of Nyepi in Bali - Arsawati, Ni Nyoman Juwita (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
Constitution of the Republic of Indonesia 1945 on Regional Government, especially in Article 18 and paragraph (2) states that "the state recognizes and respects units of customary law communities along with their traditional rights as long as they still live, and in accordance with the development of society and the principles of the Republic of Indonesia, which is regulated by law ". In response to these provisions, the Bali provincial government released Regional Law 3 of 2003 on Pakraman and Customs Agency by sticking to the philosophy of "Tri Hita Karana". In maintaining security and public order Pakraman in Bali, a task force was formed traditionally called "pecalang", which means "celang" (the sharpness of the senses). Pecalang becomes one device of Pakraman, due to the formation through village Paruman (meeting) based on the teachings of Hinduism. Not all citizens can be pecalang of Pakraman, but the election is carried out by village prajuru based on Paruman stated in the villages "awig awig" (law). Therefore, based on the concept of "ngayah" (notÂ  paid), a pecalang in any activities is related to customs, religion, and other activities withÂ  national and international scope, are required to participate in maintaining security and order of Pakraman, the area where pecalang domiciled. Especially on Nyepi, pecalang in maintaining security and order in each Pakraman both the physical environment, socio-cultural environment, including the behavior of the villagers, still do a good cooperation with the police of state and the entire community in Pakraman with coordination on any activities carried out.